2007
DOI: 10.1038/sj.ijo.0803676
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of expression of adiponectin receptors in human adipose tissue depots and its relation to the metabolic state

Abstract: Objective: To investigate whether adiponectin receptor genes (AdipoR1 and AdipoR2) expression in human subcutaneous (SAT) and visceral (VAT) adipose tissue in severely obese patients with or without diabetes is related to adiponectin gene (APM1) expression and in vivo metabolic parameters. Design: Cross-sectional, clinical research study. Subjects: Total RNA was extracted from SAT and VAT tissue obtained during surgery from 13 lean controls, 30 obese diabetic patients, 19 obese glucose-intolerant patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 45 publications
3
37
1
4
Order By: Relevance
“…In the current study, the mRNA as well as the protein expression of ACRP30 and its two receptors did not differ between VAT and SAT in severely obese patients. Accordingly, it was reported that both ACRP30 receptors are similarly expressed between VAT and SAT (25). However, a decreased ADIPOR1 expression in SAT compared with VAT was also described in obese patients (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, the mRNA as well as the protein expression of ACRP30 and its two receptors did not differ between VAT and SAT in severely obese patients. Accordingly, it was reported that both ACRP30 receptors are similarly expressed between VAT and SAT (25). However, a decreased ADIPOR1 expression in SAT compared with VAT was also described in obese patients (26).…”
Section: Discussionmentioning
confidence: 99%
“…Together with the well-known endocrine role of ACRP30, an autocrine/paracrine role has also been suggested (24); in fact, both ACRP30 receptors have been identified in adipose tissues, but their relative expression in VAT and SAT remains to be defined (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, serum adiponectin levels are inversely correlated with waist circumference and intra-abdominal fat accumulation (48), suggesting that depot differences likely exist in adiponectin secretion. Depot differences in adiponectin gene expression have been reported by some (23,46,49) but not all investigators (18,53,63) and importantly are not always correlated with AT secretion (49) or circulating levels (30). Little is known regarding posttranscriptional regulation of adiponectin.…”
mentioning
confidence: 99%
“…Similarly, both adiponectin receptors are expressed (mRNA) in human adipose tissue and in isolated adipocytes from both subcutaneous and omental depots. Their levels correlate negatively with indices of obesity and metabolic dysfunction and are increased by physical exercise (Rasmussen et al, 2006, Nannipieri et al, 2007, Blüher et al, 2007. However, expression of the receptors is not proof of locally acting adipokines.…”
mentioning
confidence: 99%